NILAI-NILAI PANCASILA DALAM KEHIDUPAN SEHARI-HARI - Elghin Chelsea Al-ghistni, Elghin; Slam, Zaenul (Kajian Moral dan Kewarganegaraan, 2026)
National and state life is guided by the noble values contained in Pancasila, the ideology and foundation of the Indonesian state. In this article, we talk about how the values contained in Pancasila can be applied in the daily lives of Indonesians to help maintain unity, harmony and social justice. Values such as divinity, humanity, unity, populism and social justice are explained in ways that can be practiced by everyone. A harmonious, tolerant and just society can be created by understanding what Pancasila is all about. The article also emphasizes how important Pancasila-based character education is to form an honest and responsible generation. In addition, it notes the challenges associated with the application of Pancasila in this day and age. It is the conclusion of the article that the values of Pancasila serve not only as a symbol of nationhood but also as an outline of actions that can be applied to build a peaceful and prosperous social life.Keywords: Pancasila Values, Daily Life, Application of Pancasila.